IWIPP Proceedings. IEEE International Workshop on Integrated Power Packaging (Cat. No.98EX203)
DOI: 10.1109/iwipp.1998.722311
|View full text |Cite
|
Sign up to set email alerts
|

Al/SiC baseplate hybrid power modules: evaluation of the thermomechanical performances

Abstract: This paper deals with an evaluation of the performances of hybrid power modules using AvSiC Metal Matrix Composite (MMC) baseplates. In this study, we analyse the possible damage in the assemblies by measuring their thermal resistance. Results show that even after 2700 thermal shocks, only a very small increase of the thermal resistance of the assemblies is observed In comparison, modules with copper baseplates show a strong increase of the thermal resistance and fail well before. As a consequence, in applicat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(1 citation statement)
references
References 4 publications
0
1
0
Order By: Relevance
“…Aluminum matrix composites reinforced with high volume fraction of SiC particles provide a novel solution to electronic packaging and thermal management applications[I, 4,5], because of their high thermal conductivity, compatible and tailaborable CTEs, lightweight, enhanced specific strength and modulus. It has been reported that the lifetime limitation of hybrid power modules can be improved more than 10 times by replacing copper baseplate with SiCp/AI composite [6].…”
Section: A Materialsmentioning
confidence: 99%
“…Aluminum matrix composites reinforced with high volume fraction of SiC particles provide a novel solution to electronic packaging and thermal management applications[I, 4,5], because of their high thermal conductivity, compatible and tailaborable CTEs, lightweight, enhanced specific strength and modulus. It has been reported that the lifetime limitation of hybrid power modules can be improved more than 10 times by replacing copper baseplate with SiCp/AI composite [6].…”
Section: A Materialsmentioning
confidence: 99%